Raspberry Pi Assembly language programming : ARM processor coding - Smith, Stephen (Technology in action series., 2019)
Gain all the skills required to dive into the fundamentals of the Raspberry Pi hardware architecture and how data is stored in the Pis memory. This book provides you with working starting points for your own projects while you develop a working knowledge of Assembly language programming on the Raspberry Pi. You'll learn how to interface to the Pis hardware including accessing the GPIO ports. The book will cover the basics of code optimization as well as how to inter-operate with C and Python code, so you'll develop enough background to use the official ARM reference documentation for further projects. With Raspberry Pi Assembly Language Programming as your guide you'll study how to read and reverse engineer machine code and then then apply those new skills to study code examples and take control of your Pis hardware and software both.